Optimalization of PHBS (Clean and Healthy Living Behavior) with the Formation of Cilik Nurses at SD Sei Petani Medan - Santosa, Heru; Imelda, Fatwa; Lumbanraja, Sarma Nursani (Talenta Publisher, 2023)
Elementary School Sei Petani is a experimental elementary school located in Medan City, North Sumatra with 34 teachers and 326 students and 355 students. PHBS activities at school have the benefit of being able to create a clean and healthy environment, improve the teaching and learning process and students, teachers and the school community become healthy. The problems found are that SD Sei Petani does not have a UKS room at school, SD has never conducted routine health education, students have not received training on Little Nurses. Students have never been given knowledge to perform first aid in accidents (P3K), weight and height measurements are not routinely carried out per 6 months, schools do not provide guidance on school stalls, hand washing with soap activities have never been carried out routinely at school, toilets and school bathrooms are not cleaned regularly, landfills do not meet health requirements. The purpose of this community service is Optimizing PHBS (Clean and Healthy Living Behavior) with the Formation of Little Nurses at SD Sei Petani Medan. Stages of implementation method with 5 stages of activity. activity 1 identifying students' knowledge about PHBS at school, activity 2 education about 8 PHBS activities at school, activity 3 empowering students to become Little Nurses to improve their knowledge and skills as a mobilizer to other students procuring UKS facilities and infrastructure. Activity 4 Procurement of UKS facilities and infrastructure, activity 5 fostering a healthy school environment, namely supervision of garbage, toilets / bathrooms, cleanliness of the school environment and school canteens. The solution offered from the above problems is to empower students by forming little nurses and conducting training for Little Nurses as drivers and supervisors of healthy living behavior in schools, procuring UKS facilities and infrastructure, fostering a healthy school environment, namely supervision of garbage, toilets / bathrooms, cleanliness of the school environment and school canteens.